Mark. A theological exposition of sacred Scripture - C.C. Caragounis (Acta Theologica)
Read a review of Voelz, J.W., (Concordia Commentary), (Concordia Publishing House, Saint Louis, 2013), Mark 1:1- 8:26, ISBN: 0758603142, Mark 8:27 – 16:20, ISBN: 0758639554.